The Human Being As The Philosophical Problem of Arts - Khalykov, K.; Nussipzhanova, B. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
The article analyzes the problem of the relationship of philosophers and artists of different times to the being of a person and works of art. As well as contemporary art, which is not looking for ideals in general, and, furthermore, intends to show more ugly things then beautiful. When we say «ideal», we meaning that in a particular human life, it does not play a role as a kind of a priori givens, which is objectified in practice and mind. We understand it as a kind of image of the «perfect» and «perfection», which in special cases exerts its action in the creative arts, in artistic creativity as a stimulant beginning of life. Therefore, we consider the architectonic of art as something that modeling world, along with the designing the form of a human being as a spiritual and individual, defines the world of man and his existence as the main measure and value. Fundamental human being basis may provide contemporary art to link to the world in a new context, as well as the importance of communication in relation of the «I» to the «Other» in the deepest sense. Key words: human being, aesthetical categories ‘ideal’and ‘ugly’,‘perfect’, ‘perfection’, Prague Quadrennial (PQ).